PENGARUH KEHILANGAN GIGI POSTERIOR TERHADAP KUALITAS HIDUP INDIVIDU LANJUT USIA STUDI TERHADAP INDIVIDU LANJUT USIA DI UNIT REHABILITASI SOSIAL PUCANG GADING DAN PANTI WREDHA HARAPAN IBU SEMARANG - Gilang Satria Wardhana; Moh. Baehaqi; Rizki Amalina (Faculty of Dentistry, Universitas Islam Sultan Agung, 2015)
Background: Elderly is an individual who has reached the age of 60 years and above. The aging process causes changes in the physical condition of the individual and affect the structure of the oral cavity includes the function of teeth, jaws and other oral tissues. Loss of teeth leads to reduced ability to chew, bite, talk and decrease a person's confidence. Quality of life is the individual response to physical function, psychological and social to their everyday lives. Oral Health Related Quality of Life can be measured by several kinds of questionnaires, one of them is OHIP - 14. Purpose: The aim of this study are to determine impact of losing posterior teeth on quality of life on elderly individuals between tooth loss <3 posterior teeth with tooth loss <3 posterior teeth in an arch. Method: The research method was analytic observational cross-sectional approach. The sample in this study were 40 individuals who were divided into two groups, group A elderly individuals with posterior tooth loss < 3 in one arch and group B elderly individuals with posterior tooth loss < 3 in one arch. Analysis of the data in this study was using a non-parametric test with Kolmogorov -Smirnov test with p < 0.05. Result: Based on the Kolmogorov -Smirnov test , concluded there are significant differences between groups A and group B ( p < 0.05 ). Conclusion: From the results of this study concluded that elderly individuals with posterior tooth loss < 3 in the arch have a better quality of life. Group b elderly individuals with posterior tooth loss ≥ 3 in the arch have a lower quality of life.